DETERMINATION OF THE LEVEL OF RISKS IN INVESTMENT PROJECTS USING ECONOMETRIC MODEL - Baxriddin Jurayevich, Mahmudov; Bahromjon Ibroximovich, Rakhimov (International Journal of Business, Law, and Education, 2020)
Particular study of the effective use of investments, including foreign investments, on technical and technological modernization of enterprises and diversification of products in the conditions of modernization of the economy, ensuring the competitiveness of manufactured products and services in the world market is one of the most important tasks of today. Today, further reforming and liberalizing the Uzbek economy should accelerate the improvement of the investment climate in the industrial sector, especially with the development of the private sector.